نظام الكتروني لمتجر " Reema Handmade - نضال حلواني, دانه; سلطان, شهد; المحتسب, نور (جامعة بوليتكنك فلسطين - نظم معلومات, 2022)
يهدف المشروع إلى تصميم و بناء موقع لنظام الكتروني يمّكن من خلاله عمليات البيع والشراء والدفع والتوصيل عبر الانترنت، ومن خلال موقعنا "Reema handmade " يتمكن التاجر من عرض منتجاته وخدماته ويستطيع الزبون التسوق بسهولة . ويمكن للمستخدم استعراض المنتجات المعروضة على النظام وإمكانية شرائها ،كما يمكن للزبائن طلب أي منتج أونلاين، ويسهّل عملية إدارة المنتجات في النظام. The Abstract The goal of the project is to design and create a website for an electronic market that allows merchants to sell, buy, pay, and deliver goods over the Internet using our "Reema handmade " website. He will display his products and services, so the customer can easily shop. The user can review the products displayed on the system and purchase them , and order any product online and have it delivered to their door. It facilitates the process of managing products on the site easier.
no of pages 122 , نظم معلومات 2022
Keywords: الانظمة الالكترونية